Characteristics of Dual‐Gate Graphene Thermoelectric Devices Based on Voltage Regulation. Issue 7 (14th June 2020) - Wang, Ning; Ma, Zhihao; Ding, Can; Jia, Hongzhi; Sui, Guorong; Gao, Xiumin
Abstract : The bandgap, the carrier concentration, and the polarity in graphene can all be controlled by gate voltage, which provides a new opportunity for the study of the regulation of thermoelectric devices. Herein, a dual‐gate thermoelectric device model for graphene with top‐gate and back‐gate structures is proposed. Based on the influence of gate voltage on carrier concentration and the Fermi level, the relationship between the gate voltage and the channel resistance, the Seebeck coefficient, and the conductivity of dual‐gate graphene, thermoelectric devices are established according to the mechanism of carrier transport. The results demonstrate that the optimal voltage window of the Seebeck coefficient, conductivity, and power factor is obtained independently. Compared with the conventional graphene thermoelectric device without the top‐gate structure, the Seebeck coefficient and the power factor for the proposed dual‐gate structure are increased twofold and tenfold, respectively. Herein, a new approach is provided for high‐performance thermoelectric device designs with accurate regulation. Abstract : Herein, a dual‐gate thermoelectric device model for graphene with top‐gate and back‐gate structures is proposed. Based on theoretical analysis, it is found that a dual‐gate structure not only has flexible and accurate controllability, but also the thermoelectric performance parameters are substantially enhanced. Compared with the back‐gate structure, the power factor increases from 0.05 to 0.55 W cm −1 K −2 .